Discontinuation of follow-up care for young people with complex chronic conditions: conceptual definitions and operational components - Sandra Skogby; Ewa-Lena Bratt; Bengt Johansson; Philip Moons; Eva Goossens (BMC, 2021)
Abstract Background A substantial proportion of young people with Complex Chronic Conditions (CCCs) experience some degree of discontinuation of follow-up care, which is an umbrella term to describe a broken chain of follow-up. Discontinuation of follow-up care is not clearly defined, and the great plethora of terms used within this field cannot go unnoticed. Terms such as "lost to follow-up", "lapses in care" and "care gaps", are frequently used in published literature, but differences between terms are unclear. Lack of uniformity greatly affects comparability of study findings. The aims of the present study were to (i) provide a systematic overview of terms and definitions used in literature describing discontinuation of follow-up care in young people with CCC's; (ii) to clarify operational components of discontinuation of follow-up care (iii); to develop conceptual definitions and suggested terms to be used; and (iv) to perform an expert-based evaluation of terms and conceptual definitions. Methods A systematic literature search performed in PubMed was used to provide an overview of current terms used in literature. Using a modified summative content analysis, operational components were analysed, and conceptual definitions were developed. These conceptual definitions were assessed by an expert panel using a survey. Results In total, 47 terms and definitions were retrieved, and a core set of operational components was identified. Three main types of discontinuation of follow-up care emerged from the analysis and expert evaluation, conceptually defined as follows: Lost to follow-up care : "No visit within a defined time period and within a defined context, and the patient is currently no longer engaged in follow-up care"; Gap in follow-up care: "Exceeded time interval between clinic visits within a defined context, and the patient is currently engaged in follow-up care"; and Untraceability: "Failure to make contact due to lack of contact information". Conclusion By creating a common vocabulary for discontinuation of follow-up care, the quality of future studies could improve. The conceptual definitions and operational components provide guidance to both researchers and healthcare professionals focusing on discontinuation of follow-up care for young people with CCCs.